Statistical experiment analysis of wear and mechanical behaviour of abaca/sisal fiber-based hybrid composites under liquid nitrogen environment - L, Natrayan; Surakasi, Raviteja; Paramasivam, Prabhu; Dhanasekaran, Seshathiri; S., Kaliappan; Patil, Pravin P. (Frontiers in Materials, 2023)
Composite materials are increasingly replacing synthetic fiber combinations in various applications. However, certain extreme environments on Earth and in space require structures to operate under low temperatures, specifically cryogenic conditions, which can significantly affect material reactions. Therefore, the main focus of this study is to develop and evaluate hybridized biocomposites, specifically assessing their tensile, bending, and impact strengths in a controlled liquid nitrogen environment (77 K). Utilizing the Taguchi optimization method, the statistical analysis of wearing characteristics was carried out utilizing cryogenic treatment hours, load, sliding distance, and weight percentage of abaca and sisal fibers. When 20 percent abaca and sisal were mixed, tensile performance increased from 28.96 to 36.58 MPa. Likewise, the same mixture increased bending strength from 59.63 to 75.68 MPa, and impact strength improved from 59.36 to 71.25 J/m. The cryogenic treatment of composite materials for 15–30 min improved the mechanical characteristics of the materials by enhancing the binding between reinforcements and substrate. The Taguchi 27 test outcomes showed a decreased friction coefficient of 7.79 × 105 mm3/Nm in the 10th trial with 30 min of cold working, 10% hybrid fibers, 600 m slide distance, and a 4 N load combination. Frictional coefficient data indicated the lowest rate during the third experiment with 15 min of cryogenic treatment, 10% hybrid fibers, 1,500 m slide length, and a 12 N load combination. The microstructural analysis of the fractured specimen was evaluated by scanning electron microscopy. Finally, such composite materials are employed in liquid propellant tanks, satellites, spaceships, rocket constructions, aeroplane components at cruising altitudes, and other applications.